INTERACTION BETWEEN GOVERNMENT EXPENDITURE, GOOD GOVERNANCE, AND ECONOMIC GROWTH IN THE ASIA AND AFRICA REGION - Dwi Tri Mega Rahayu; Andryan Setyadharma; Shanty Oktavilia (Business and Economic Analysis Journal, 2024)
This research is motivated by the gap phenomenon in Asia and Africa, where there is a discrepancy between theory and previous research and the reality in these two regions. Based on government governance data, Asia and Africa have institutional qualities that could be better than other regions in the world. However, poor institutional quality does not reduce economic growth in the Asian and African regions. This research uses data from the World Bank and World Governance Indicators for the 2000-2022 period using variables of government governance, government spending, and economic growth. This research uses the FMOLS method using Eviews 10. The research results show that political stability, regulatory quality, and control of corruption have a positive and significant effect on economic growth in the Asian and African regions. Meanwhile, the effectiveness of government performance and the rule of law positively and significantly impact economic growth in the Asian region but do not influence the African region. The research results on the voice and accountability variables show no influence on economic growth in the Asian region. Still, the African region positively and significantly impacts economic growth.